On Bedload and Suspended Load Measurement Performances in Sheet Flows Using Acoustic and Conductivity Profilers. Issue 10 (24th October 2018) - Fromant, G.; Mieras, R. S.; Revil‐Baudard, T.; Puleo, J. A.; Hurther, D.; Chauchat, J.
Abstract: Intense sediment transport experiments were performed in a gravity‐driven open‐channel flow with two sizes of uniformly distributed nonspherical acrylic particles having median diameters of 1.0 and 3.0 mm and a maximum packing volumetric concentration ( ϕ ) of 0.55. The flow conditions were adapted to each particle size to ensure similar sediment transport flow regimes as sheet flow corresponding to Shields numbers slightly above unity and a suspension number, ratio of settling velocity to friction velocity, near unity for the two experiments. An acoustic scattering‐based system (Acoustic Concentration and Velocity Profiler) and conductivity probes (Conductivity Concentration Profiler [CCP]) with two different vertical resolutions, 1 mm (CCP1mm ) and 2 mm (CCP2mm ) were used to measure instantaneous concentration profiles across the bedload and suspension layers. Measured concentration profiles, bed interface position, and sheet flow layer thicknesses are compared between the two techniques. The capabilities and limitations of both technologies are outlined. Average volumetric sediment concentration profiles were overestimated by 10% with the Acoustic Concentration and Velocity Profiler in the dense sheet layer when ⟨ ϕ ( z )⟩≳ 0.35, and by 100% with the CCP in the more diluted region when ⟨ ϕ ( z )⟩≲ 0.015 and ⟨ ϕ ( z )⟩≲ 0.20 for CCP1mm and CCP2mm, respectively. Good agreement is found between the three systems in terms of average and time‐resolved bed level position and sheet layer thickness, validating the different bed interface detection methods on data from the two sensors. Key Points: A comparative analysis of acoustic and conductivity‐based measurements was done under sheet flow conditions with two acrylic particle sizes CCP and nonintrusive ACVP concentrations were measured across the dilute suspension and sheet layer with relative errors of less than 10% Different ACVP and CCP bed detection methods to estimate the sheet layer thickness agree within two to three particle diameters